Usability testing of “smart odontogram” application based on user’s experience - Brahmanta, Arya; Maharani, Aulia Dwi; Dewantara, Bima Sena Bayu; Sigit, Riyanto; Sukaridhoto, Sritrusta; Fadhillah, Excel Daris (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Collecting dental data for odontogram in medical records is done chiefly conventionally and causes a lot of human errors. Disadvantages of the conventional method can be overcome by developing a server-based system to store medical information equipped with embedded artificial intelligence (AI), which can identify the patient’s dental condition using an intra-oral camera with the help of Deep Learning algorithms. It is essential to evaluate the usability of this application to adapt to user needs. This study aimed to know the user’s experience in using this application and also provide information for improvements of the application. Methods: This is quantitative descriptive research with 15 users (dentists) as the respondent. The questionnaire was used to measure the user’s experience using this application. The user’s experiences measured are effectivity, efficiency, and satisfaction. Results: The highest scores of respondents on the three variables are extremely efficient, effective, and satisfied (9 people). The lowest score is slightly efficient and neutral on the efficiency and effectiveness variables (0 people). In the satisfaction variable, the lowest score is slightly satisfied (0 people). Conclusions: The Usability Testing of the “Smart Odontogram” Application based on User’s Experience showed a good result in 3 variables: effectiveness, efficiency, and satisfactionKeywords: smart Odontogram; medical record; application; usability testing; user’s experience